High-intensity activity according to playing position with different team formations in soccer - Vilamitjana, J. J.; Heinze, G.; Verde, P.; Calleja-Gonzalez, J. (Acta Gymnica, 2021)
Background: A tactical factor such as playing formation seems to be another influencing factor in the physical performance of elite soccer players during the match. Some researchers have suggested that distances covered during high-intensity running in matches are valid measures of physical performance. They concluded that players covered greater distances of high-intensity activities during some team formations in comparison to others.